Globalization and human nutrition: opportunities and risks for the poor in developing countries - Pinstrup-Andersen, Per; Babinard, Julie (Rural Outreach Program, 2001)
This paper provides a conceptual framework for assessing the linkages between globalizationa and nutrition and suggests action to be taken by governments and civil society. -- Abstract